2021
DOI: 10.2147/dddt.s326891
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dezocine and Sufentanil on Th1/Th2 Balance in Breast Cancer Patients Undergoing Surgery

Abstract: Background: It is very important for breast cancer patients undergoing surgery to choose an opioid that has little effect on the immune system. The aim of this study is to compare the effects of dezocine or sufentanil on postoperative pain and Th1/Th2 balance in patients undergoing breast cancer surgery. Methods: Data from 92 breast cancer patients from January 2019 to July 2020 at Foshan Second People's Hospital (Guangdong, China) were analyzed. Sufentanil (SF) was used in group SF (n = 44) and dezocine (DE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“… 52 Studies have also found that dezocine maintains the balance of serum Th1/Th2 cytokines (INF-γ/IL-4) better than sufentanil in patients with gastric cancer surgery 64 and downregulates the expression of the TNF-α and IL-6 inflammatory factors in patients with liver cancer surgery. 65 Our studies also found that dezocine inhibits CRP levels 66 and maintains the CD3+/CD8+ balance, the IL-2/IL-10 cytokine balance 67 , 68 and the Th1/Th2 cell balance 69 in breast cancer patients undergoing surgery as compared to fentanyl or sufentanil. Interestingly, Dong et al found that the production of IFN-γ and PD-L1 decreases after treatment with 2 µg/mL dezocine but increases after treatment with 8 µg/mL dezocine in lung cancer cells, 70 suggesting that clinical doses of dezocine have immune upregulation effects but that large doses lead to immunosuppression, which is consistent with our previous findings.…”
Section: Dezocine Has Potential To Regulate the Clinical And Biologic...supporting
confidence: 57%
“… 52 Studies have also found that dezocine maintains the balance of serum Th1/Th2 cytokines (INF-γ/IL-4) better than sufentanil in patients with gastric cancer surgery 64 and downregulates the expression of the TNF-α and IL-6 inflammatory factors in patients with liver cancer surgery. 65 Our studies also found that dezocine inhibits CRP levels 66 and maintains the CD3+/CD8+ balance, the IL-2/IL-10 cytokine balance 67 , 68 and the Th1/Th2 cell balance 69 in breast cancer patients undergoing surgery as compared to fentanyl or sufentanil. Interestingly, Dong et al found that the production of IFN-γ and PD-L1 decreases after treatment with 2 µg/mL dezocine but increases after treatment with 8 µg/mL dezocine in lung cancer cells, 70 suggesting that clinical doses of dezocine have immune upregulation effects but that large doses lead to immunosuppression, which is consistent with our previous findings.…”
Section: Dezocine Has Potential To Regulate the Clinical And Biologic...supporting
confidence: 57%
“…Th2 cells can promote B cell maturation, proliferation, and antibody production to exert anti-tumor effects [18]. We evaluated the role of Th2 cell-mediated activation of B cells in CRC.…”
Section: Plos Onementioning
confidence: 99%
“…Accumulating evidence suggests that the selection of anaesthetic drugs, approaches and time can exert diverse repercussions on the immune system. For instance, intravenous injection of dezocine can elevate the Th1/Th2 cell ratio after breast cancer surgery 97 . The ratio of Th1/Th2 cells is associated with tumour growth, metastasis and survival, and the shift to Th1 cells tends to usher in a more desired immune response against cancer 98 .…”
Section: Anticancer Immune Response Outside the Tumourmentioning
confidence: 99%
“…For instance, intravenous injection of dezocine can elevate the Th1/Th2 cell ratio after breast cancer surgery. 97 The ratio of Th1/Th2 cells is associated with tumour growth, metastasis and survival, and the shift to Th1 cells tends to usher in a more desired immune response against cancer. 98 These findings suggest an underappreciated role of anaesthesia in cancer immune response, which warrants further investigation.…”
Section: Anticancer Immune Response Outside the Tumourmentioning
confidence: 99%